The Legend of Kemaro Island for Supporting Students in Learning Average - Lestariningsih Lestariningsih; Ratu Ilma Indra Putri; Darmawijoyo Darmawijoyo (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2012)
This research is aimed to determine the role of Indonesian folklore context namely the Legend of Kemaro Island in supporting average learning on 6-grade students with Pendidikan Matematika RealistikIndonesia (PMRI) approach. The method used is design research that contains three stages namely preliminary design, teaching experiment, and retrospective analysis. Results from the research show that Indonesian folklore context can support students to develop their knowledge in the concept of average. Strategy and model (emergent modeling) that students discover, describe and discuss the construction or contribution shows how students can use to help their initial understanding of the concept of average.